De la désindustrialisation au scandale de la France contaminée - Sylvain Le Berre; Sophie Bretesché (VertigO)
The chronology of the media coverage and the trajectory of the media discourse on the post-mining of French uranium, based on an emblematic case of the national policy of post-exploitation management (Bessines), highlights the strength of the territory and of the local agenda in defining a public issue. We also understand the role of crossing the different media arenas in the process of putting into words the controversy.